2023
DOI: 10.1038/s41598-023-39677-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and analysis of surface deformation in alpine valley areas based on multidimensional InSAR technology

Abstract: Joshimath has received much attention for its massive ground subsidence at the beginning of the year. Rapid urbanization and its unique geographical location may have been one of the factors contributing to the occurrence of this geological disaster. In high mountain valley areas, the complex occurrence mechanism and diverse disaster patterns of geological hazards highlight the inadequacy of manual monitoring. To address this problem, the inversion of deformation of the Joshimath surface in multiple directions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Second, localized deformation zones with dimensions <12 m as observed in the field are beyond the InSAR resolution limit (30 m). Similar to our results, Yang et al (2023) also did not observe notable change in the InSAR time-series during November 2022 and January 2023. Conversely, Shankar et al (2023) showed comparable results between GPS and Sentinel-1 InSAR (descending) observations.…”
Section: Landslide Mobility and Rainfallsupporting
confidence: 91%
See 2 more Smart Citations
“…Second, localized deformation zones with dimensions <12 m as observed in the field are beyond the InSAR resolution limit (30 m). Similar to our results, Yang et al (2023) also did not observe notable change in the InSAR time-series during November 2022 and January 2023. Conversely, Shankar et al (2023) showed comparable results between GPS and Sentinel-1 InSAR (descending) observations.…”
Section: Landslide Mobility and Rainfallsupporting
confidence: 91%
“…Our analysis reveals that the episodic accelerations of the Joshimath landslide are triggered by extreme rain events. However, Yang et al (2023) suggested that the 4.7 magnitude earthquake that occurred on 11 September We note that the reported earthquake epicenter is about 28 km away from the Joshimath town and there are no significant earthquakes (M > 5) within 30 km for the past 20 years that correlate with the previous episodes of landslide acceleration (Figures 2c and 3d and Figure S1a in Supporting Information S1). Hence, it is difficult to reconcile the role of earthquakes in the mobility of Joshimath landslide.…”
Section: Kinematics Of Joshimath Landslide and Implicationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Also, we have validated two landslide sites L-1 and L-2 (Figure ), with GoogleEarth Pro. The observed deformation rate in both orbits can vary due to sensor Line of Sight (LOS), topography of the terrain and incidence angle of orbit's acquisition geometry [18].…”
Section: Deformation Analysis Of Koldam Reservoirmentioning
confidence: 99%
“…Taiyuan City and Yuncheng City, which have large annual change rates of GWS, were selected as the key areas for extracting surface deformation features, and the SAR images covering Taiyuan City and Yuncheng City were pre-processed and decoded respectively. To obtain interferometric pairs with higher coherence, the maximum temporal baseline was set to 150 and 100 days, respectively, and the maximum spatial baseline to 10% of the critical baseline [48], [49]. The spatial baseline connectivity of the image pairs is shown in Figure 11, where the X-axis represents the date, the Y-axis represents the baseline distance between the two view images, and the red and green dots represent the distribution of the primary and secondary images on the time series, respectively.…”
Section: The Relationship With Regional Surface Deformationmentioning
confidence: 99%